Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year Three, 2013 – Agriculture, Climate and Employment - Tvedten, Inge; Rosário, Carmeliza; Tuominen, Minna; Samuel Jones (ORGUT Consulting AB, 2013)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; institutions / instituições; poverty / pobreza

Support to Civil Society Engagement in Policy Dialogue - Ministry of Foreign Affairs of Denmark (SIDA, 2013)
This evaluation, the ‘Joint Evaluation of Support to Civil Society Engagement in Policy Dialogue’ was initiated by the Donor Group on Civil Society and Aid Effectiveness. Specifically it was commissioned by three Development Partners (DPs), ADC/Austria, Danida/Denmark and Sida/Sweden, which form the Management Group. A larger group of bilateral DPs support the evaluation through their participation as the international Reference Group. The evaluation took place between June 2011 and September 2012. The Evaluation Team was drawn from the consulting firm ITAD Ltd in the UK (lead firm), together with experts from COWI (Denmark) and experts from each of the three countries selected for the fieldwork, Bangladesh, Mozambique and Uganda. The purpose of this evaluation is lesson learning, to help DPs gain a better understanding of how best to support Civil Society Organisations (CSOs) in the area of policy dialogue. The findings will also have direct relevance to the CSOs in the three countries and the wider CSO community, as well as the Governments and local authorities interacting with Civil Society (CS) representatives. The evaluation focuses on: 1. How CSOs engage in policy dialogue and the relevance and effectiveness of their policy work; 2. the enabling environment, that is the enablers and barriers to CSO engagement; and 3. how different DP support strategies may influence CSOs’ ability to engage in policy dialogue, and how best the DPs might support CSO policy dialogue in the future.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; citizenship & participation / cidadania e participação; civil society / sociedade civil